The influence of drought on flow‐ecology relationships in Ozark Highland streams. (8th March 2018) - Lynch, Dustin T.; Leasure, Douglas R.; Magoulick, Daniel D.
Abstract: Drought and summer drying can have strong effects on abiotic and biotic components of stream ecosystems. Environmental flow‐ecology relationships may be affected by drought and drying, adding further uncertainty to the already complex interaction of flow with other environmental variables, including geomorphology and water quality. Environment–ecology relationships in stream communities in Ozark Highland streams, USA, were examined over two years with contrasting environmental conditions, a drought year (2012) and a flood year (2013). We analysed fish, crayfish and benthic macroinvertebrate assemblages using two different approaches: (1) a multiple regression analysis incorporating predictor variables related to habitat, water quality, geomorphology and hydrology and (2) a canonical ordination procedure using only hydrologic variables in which forward selection was used to select predictors that were most related to our response variables. Reach‐scale habitat quality and geomorphology were found to be the most important influences on community structure, but hydrology was also important, particularly during the flood year. We also found substantial between‐year variation in environment–ecology relationships. Some ecological responses differed significantly between drought and flood years, while others remained consistent. We found that magnitude was the most important flow component overall, but that there was a shift in relative importance from low flow metrics during the drought year to average flow metrics during the flood year, and the specific metrics of importance varied markedly between assemblages and years. Findings suggest that understanding temporal variation in flow‐ecology relationships may be crucial for resource planning. While some relationships show temporal variation, others are consistent between years. Additionally, different kinds of hydrologic variables can differ greatly in terms of which assemblages they affect and how they affect them. Managers can address this complexity by focusing on relationships that are temporally stable and flow metrics that are consistently important across groups, such as flood frequency and flow variability.